Rupture of the caecum due to invasive amoebiasis - Mahmud, Rohela; Lee, Amir; Anuar, Khairul; Nor, Zurainee Mohamed; Surin, Johari (Faculty of Medicine, University of Malaya, 2000)
This paper describes a case of invasive amoebiasis in a 72 year old woman. About 1 week prior to admission she had right iliac fossa pain and physical examination suggested perforated appendix or carcinoma of caecum. Laparotomy revealed perforation of caecum. Histopathology of tissue removed showed abundant trophozoites of Entamoeba histolytica. After surgery treatment was instituted and patient had an uneventful recovery.